2021
DOI: 10.1186/s41021-021-00182-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new quantitative structure–activity relationship model for predicting Ames mutagenicity of food flavor chemicals using StarDrop™ auto-Modeller™

Abstract: Background Food flavors are relatively low molecular weight chemicals with unique odor-related functional groups that may also be associated with mutagenicity. These chemicals are often difficult to test for mutagenicity by the Ames test because of their low production and peculiar odor. Therefore, application of the quantitative structure–activity relationship (QSAR) approach is being considered. We used the StarDrop™ Auto-Modeller™ to develop a new QSAR model. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The ICH-M7 guideline also allows the use of the quantitative structure–activity relationship ((Q)SAR) approach for the initial assessment of genotoxicity instead of the Ames test. We have developed and validated some (Q)SAR tools for assessing the genotoxicity of food-flavoring chemicals, demonstrating good correlation between the (Q)SAR and Ames results [6] , [7] , [8] , [14] . We believe that (Q)SAR will be widely accepted in the field of genotoxicity as an alternative to the Ames test in the near future.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The ICH-M7 guideline also allows the use of the quantitative structure–activity relationship ((Q)SAR) approach for the initial assessment of genotoxicity instead of the Ames test. We have developed and validated some (Q)SAR tools for assessing the genotoxicity of food-flavoring chemicals, demonstrating good correlation between the (Q)SAR and Ames results [6] , [7] , [8] , [14] . We believe that (Q)SAR will be widely accepted in the field of genotoxicity as an alternative to the Ames test in the near future.…”
Section: Resultsmentioning
confidence: 96%
“…Table 1 summarizes the results of the Ames test, CA test, MN test, and TG assay. The Ames test data have already been reported in a previous study [14] , and the raw data of the Ames test are available in the additional file of the study. The CA test, MN test, and TG assay were conducted in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, cinnamaldehyde showed a similar response, i.e., the maximum revertant frequency in the TA100 strain in the absence of S9-mix was slightly more than twice that in the negative control. Trans-cinnamaldehyde (cas# 104–55-2), 4′-methoxy cinnamaldehyde (cas#1963-36-6), and benzalacetone (4-phenyl − 3-buten-2-one; cas# 122–57-6), which are cinnamaldehyde-related flavor chemicals, have also shown positive results in Ames tests [ 39 ]. We concluded that cinnamaldehyde and its derivatives are mutagenic in vitro, given that they show reproducible Ames mutagenicity and have α,β-unsaturated aldehydes.…”
Section: Discussionmentioning
confidence: 99%
“…The development of in silico methods for predicting the result of the AMES toxicity test is an active field of research in computational toxicology, and several articles have reviewed the most relevant models and software tools for predicting mutagenicity under different datasets. However, the impact that different strains used in the Ames test could have in the design of QSAR (Quantitative Structure Activity Relationship) methods has been scarcely studied. QSAR models found in the literature are trained using only overall values (i.e., toxic and nontoxic classes) resulting from the Ames test, without considering the intermediate results achieved by the experiments individually conducted for each strain.…”
Section: Introductionmentioning
confidence: 99%